PENGENDALIAN JENTIK NYAMUK PENYEBAB DBD MELALUI MODEL PENYULUHAN PARTISIPATIF DI PALEMBANG - Aseptianova Aseptianova; Saleh Hidayat; Indawan Indawan (Universitas Sebelas Maret, 2014)
The number of dengue fever patient created the apprehension from some sides. Some efforts have been done by the government starting from theterminated the vector that causes the illness i.e; eradication of wiggler, fogging, larviciding abatization and counseling about healthy behavior to residents. This research was conducted to decrease the number of wiggler or even destroy it in breeding places to decrease number of dengue fever patients. For the long term, this study aims to improve the cognitive and affective abilities of the resident and affective ability to the resident in destroying the wigglers which causes the dengue fever. This study conducted to research and development study. For the first step, the researcher did the survey, collect and analyze the data about residents’ behavior in destroying the wiggler. Second step, the researcher developed the participatory counseling to develop public awareness in destroying the wiggler. The existence of some society element such as; the head of household, RT, RW, Dasa Wisma community, Majelis Taklim, lurah, camat, Jumatik and health workers have their own effort in decreasing the wiggler. The less of their participation is exactly became the main reason of the existence of dengue fever which seems cannot be controlled by the citizen so there is always dengue fever in the society. Keywords : participatory counseling, dengue fever, wiggler